Rotator Cuff Repair With a Novel Interpositional Allograft Augmentation - Brian Forsythe MD; Vahram Gamsarian BE; Vikranth Mirle BS; Elyse J. Berlinberg BS; Harsh H. Patel BA; Hasani Swindell MD; Adam B. Yanke MD, PhD; Grant E. Garrigues MD; Christopher M. Brusalis MD (SAGE Publishing, 2023)
Background: Nearly half a million rotator cuff repairs are performed annually in the United States. Rotator cuff healing occurs at the interface between the tendon and greater tuberosity, known as the enthesis. Given that a significant number of rotator cuff tears do not heal following surgical repair, multiple adjunctive strategies have been devised to improve the structural integrity of the repaired construct. Recently, a biphasic, demineralized allograft bone implant has been developed to improve enthesis healing. Indications: Relative indications for use of tissue augmentation include greater tuberosity osteopenia, revision rotator cuff surgery, attenuated rotator cuff tissue quality, and massive rotator cuff tears. Relative contraindications include a history of infection and recent immunosuppression. Technique Description: Following preparation of the footprint with an arthroscopic burr, two triple-loaded PEEK suture anchors were placed along the medial aspect of the greater tuberosity. Sutures were then passed through the rotator cuff tendon in a horizontal mattress configuration, and each pair of suture limbs were tied along the medial row. To aid in arthroscopic passage, the biphasic graft is folded longitudinally and clamped with a curved hemostat. The graft is loaded into an arthroscopic cannula and both are delivered simultaneously through a lateral arthroscopic portal. Two 18-gauge spinal needles are placed percutaneously to fix the allograft in the desired position. Subsequently, double-row transosseous-equivalent rotator cuff repair with standard techniques is done, which provides sufficient stability to the graft. Discussion: In a series of 192 patients who underwent arthroscopic rotator cuff repair augmented with a similar bioinductive collagen implant, patients demonstrated significant improvement in patient-reported outcomes at 1 year postoperatively. Moreover, a meta analysis published in 2022 demonstrated a significantly reduced retear rate among patch-augmented rotator cuff repairs as compared to isolated rotator cuff repairs. Conclusion: Tissue augmentation can be performed efficiently and reproducibly to promote biologic healing of arthroscopic rotator cuff repairs. The specific biphasic cancellous allograft presented in this video may be a viable treatment adjunct in the setting of deficient greater tuberosity bone stock, revision cases, or impaired native enthesis healing; however, further research is needed to assess clinical outcomes associated with its use. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.